Ultrasonic Acid Digestion and Graphite Furnace Atomic Absorption Spectrometry for the Determination of Heavy Metal Ions in Tobacco - Yang1, Jie; Kong1, Weisong; Cui1, Zhuiwen; Liu1, Wei; Chen1, Yongkuan; Yang1, Guangyu; Ning1, Ping (Asian Journal of Chemistry, 2011)
An ultrasonic acid digestion and graphite furnace atomic absorption spectrometry method for the determination of trace amounts of heavy ions (chromium, nickel, cobalt, copper, cadmium and lead) in tobacco was studied. The tobacco samples were digested with ultrasonic assisted acid digestion. The parameters influencing ultrasonic assisted acid digestion, such as presonication time, sonication time, temperature of ultrasonic bath and different acid mixtures were carefully optimized. This procedure was applied to the determination of the analytes in tobacco samples with good results (recoveries greater than 95 % and RSD % lower than 3.5 %).